2014
DOI: 10.3329/bjvm.v11i1.16513
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical analysis of blood of native cattle in the hilly area of Bangladesh

Abstract: A yearlong study was carried out in indigenous cattle of five upazila namely Khagrachari Sadar, Laxmichari, Matiranga, Mahalchari and Dighinala in Khagrachari Hill District, Bangladesh for determination of statuses of various biochemical parameters. Apparently healthy cattle (100) were selected and blood samples were collected aseptically. Biochemical analysis of carbohydrates, proteins, fats, minerals, electrolytes and enzymes were performed by using automated biochemical analyzer (Humalizer ® -3000). The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 10 publications
5
12
2
Order By: Relevance
“…The higher concentration of globulin fraction may account for higher disease resistance in local cattle as compared to crossbred, further holds the view that local cattle are more disease resistant than exotic. The levels of creatinine and total proteins reported in indigenous cattle of Bangladesh by Mamun et al (2013) were higher and lower respectively as compared to the values reported in present study that suggests a healthy status of indigenous cattle of Kashmir.…”
Section: Resultscontrasting
confidence: 51%
“…The higher concentration of globulin fraction may account for higher disease resistance in local cattle as compared to crossbred, further holds the view that local cattle are more disease resistant than exotic. The levels of creatinine and total proteins reported in indigenous cattle of Bangladesh by Mamun et al (2013) were higher and lower respectively as compared to the values reported in present study that suggests a healthy status of indigenous cattle of Kashmir.…”
Section: Resultscontrasting
confidence: 51%
“…The results of biochemical investigations revealed the greatest deviations in concentrations of total serum protein, urea, Na and K which can be affected by different factors (nutrition, health status, stage of lactation and season) (Jezek et al 2013). Mamun et al (2013) were founded a slight increase of calcium, glucose and urea in female compared to the male, and alkaline phosphatase higher in growing cattle, although the variations were not significant (P>0.05). Mapiye et al (2012) were observed that most of the indigenous Nguni cattle in South Africa had urea concentration below the reference range which was possibly due to lower intakes of crude proteins on the rangeland pasture.…”
Section: Discussionmentioning
confidence: 72%
“…Data on hematological and biochemical parameters of indigenous sheep in the Indian subcontinent are limited. Few studies have been done in Indian subcontinent regarding domestic animals such as cattle [ 5 ], goat [ 6 ], buffalo [ 7 ], and small ruminants [ 8 ]. However, there is a lack of data related to the reference value for hematology and serum chemistry profiles of indigenous sheep of the Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%